Tunable Active Biquad Filter in ±0.9V 32 Nm CNFET - Tripath, S. K.; Ansari, Mohd Samar (2014 Fifth International Symposium on Electronic System Design, 2014)
In this work, design and simulation of an active biquad filter based on carbon nanotube field effect transistor is presented. The filter uses current conveyor as an active element that can work up to tens of GHz range of frequencies and could be used for high frequency applications. Moreover, filtering operations in the entire Bluetooth range (2.40 - 2.48 GHz) are demonstrated via tuning of a resistor. HSPICE simulation with 32 nm CNFET model, have been carried out to test the integrity of the design.